Firm level stock returns volatility in Malaysia: a sectoral study - Saizal Pinjaman; Sarma Aralas (2017)
This paper analyzes the level of stock returns volatility and identifies causal relationships across different economic sectors in Bursa Malaysia. We found dissimilarities of average stock returns volatility between sectors where firms in the Technology sector exhibit the highest stock returns volatility while firms in Telecommunication sector show the lowest volatility. Stock returns volatility is identified to be highly persistent, which suggests the influence of preceding shocks on current volatility level. In addition, there is evidence of leverage effects for the majority of the economic sectors, where negative news produces larger volatility when compared to positive news. Further, in the short run, the relationship of stock returns volatility between several economic sectors is found to be not statistically significant, this supports the possibility of portfolio diversification strategy to minimize risk and optimize return. However, the approach is ineffective in the long run since stock returns volatility of the economic sectors move together.